Topical (S)-ketamine for pain management of postherpetic neuralgia - Guilherme Antonio Moreira de Barros; Hélio Amante Miot; Ademir Massarico Braz; Flávia Ramos; Marcos Aristoteles Borges (Sociedade Brasileira de Dermatologia, 2012)
Herpes zoster infection may cause postherpetic neuralgia, which is defined by prolonged pain predominantly mediated by central nervous system hypersensitivity. This phenomenon may be reversed by (S)-ketamine (SKET), but its use results in intolerable side effects, while its topical administration seems to be safe. It is a cross-over design study with 12 patients randomly divided into two groups. There was a significant effect of time on pain intensity, but no statistical difference in pain scores for SKET or placebo use in this sample in this treatment regimen. Only few mild cutaneous reactions were observed with topical SKET use.